MP02: Paramedic safety culture across Eastern Ontario. (15th May 2017) - Sinclair, J.E.; Price, P.; Austin, M.A.; Reed, A.; Kwok, E.S.
Abstract : Introduction: Safety culture is defined as the shared beliefs that an organization's employees hold relative to workplace safety. Perceptions of workplace safety culture within paramedic services have been shown to be associated with patient and provider safety outcomes as well as safe work practices. We sought to characterize paramedics' perceptions of the organizational safety culture across Eastern Ontario, Canada to provide important benchmarking data to evaluate future quality initiatives.Methods: This was a cross-sectional survey study conducted September 2015-January 2016 in 7 paramedic services across Eastern Ontario. We distributed an abridged version of Patterson's previously published EMS-SAQ survey, measuring six domains of workplace safety culture, to 1, 066 paramedics during continuing medical education sessions. The questions were presented for rating on a 5 point Likert scale (1=strongly agree, 5= strongly disagree) and a response of 1 or 2 was considered a 'positive perception' response. We present descriptive statistics and chi-square tests where appropriate.Results: We received responses from 1, 041 paramedics (97.6%), with a response rate varying between 88.0% and 100% across the 8 paramedic services. One third (33.6%) were Advanced Care Paramedics (ACPs) and 39.4% of paramedics had more than 10 years' experience. The percentage of positive responses for each domain were: Safety Climate 31.2% (95% CI 28.4-34.1), Teamwork Climate 29.3% (95% CI 26.6-32.1), Stress Recognition 56.8% (95% CI 53.8-59.8), Perceptions of Management 67.0% (95% CI 64.0-69.8), Working Conditions 42.6% (95% CI 39.6-45.7), Job Satisfaction 41.6% (95% CI 38.6-44.6). Primary care paramedics had more positive perception responses for Job Satisfaction (45% vs 35%, p=0.002), whereas ACPs had more positive perception responses for Stress Recognition (61.5% vs 54.1%, p=0.022). No association was found between gender or years of experience and a positive perception of any safety domain.Conclusion: The results provide valuable workplace safety culture data that will be used to target and evaluate needed quality improvement initiatives while also raising some awareness to paramedics of important factors related to patient and provider safety.